Penggunaan Model Pembelajaran Jigsaw untuk Meningkatkan Hasil Belajar Matematika - Sunarti, Sri (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in learning mathematics through the Jigsaw learning model. This research method is classroom action research using a cycle model. Each cycle consists of 4 stages, namely: planning, implementation, observation, and reflection. This research was conducted in 2 cycles which were divided into 4 meetings. At the end of each cycle, evaluation will be carried out to determine the level of achievement and completeness of students in learning. In the pre-cycle activities, the number of students whose score is 70 (KKM) is only 30% then in the first cycle it increases to 70% and in the second cycle the student learning completeness increased to 90%. Based on these results, it can be concluded that the use of the Jigsaw Learning Model can improve mathematics learning outcomes in fifth grade students of SDN 2 Randusari.